2014
DOI: 10.1021/ml500427r
|View full text |Cite
|
Sign up to set email alerts
|

Interconversion of Functional Activity by Minor Structural Alterations in Nonpeptide AT2 Receptor Ligands

Abstract: Migration of the methylene imidazole side chain in the first reported selective drug-like AT 2 receptor agonist C21/M024 (1) delivered the AT 2 receptor antagonist C38/M132 (2). We now report that the AT 2 receptor antagonist compound 4, a biphenyl derivative that is structurally related to 2, is transformed to the agonist 6 by migration of the isobutyl group. The importance of the relative position of the methylene imidazole and the isobutyl substituent is highlighted herein. KEYWORDS:AT 2 receptor, nonpeptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
(68 reference statements)
4
9
0
Order By: Relevance
“…The antagonists 7b and 10a are indeed the first compounds to show K i values in the single digit nM range. 27,29 For comparison the AT2R antagonists 2 (C38/ M132) and 4 display K i values of 17.8 nM and 12.3 nM, respectively and PD123319 that is structurally very different from the ligands discussed herein exhibits an IC50 of 34 nM. 18,40 We have previously observed potent inhibition of Ang IIinduced neurite outgrowth from this class of AT 2 receptor antagonists at low concentrations, as compared to the corresponding K i -values.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…The antagonists 7b and 10a are indeed the first compounds to show K i values in the single digit nM range. 27,29 For comparison the AT2R antagonists 2 (C38/ M132) and 4 display K i values of 17.8 nM and 12.3 nM, respectively and PD123319 that is structurally very different from the ligands discussed herein exhibits an IC50 of 34 nM. 18,40 We have previously observed potent inhibition of Ang IIinduced neurite outgrowth from this class of AT 2 receptor antagonists at low concentrations, as compared to the corresponding K i -values.…”
Section: Discussionmentioning
confidence: 92%
“…We reported that independent of the methylene imidazole position, both an antagonist (4) and an agonist (6) could be obtained by moving the isobutyl side chain. 29 This suggests that the structural feature responsible for functionality is the spatial relationship between the imidazole ring and the isobutyl side chain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, migration of the isobutyl group of the antagonist 82 to yield compound 83 , regains the agonism. Compound 84 , where eight carbon atoms separate the two side chains serves as an agonist . However, there are exceptions to the hypothesis that a shorter distance between the side chains results in antagonism.…”
Section: Introductionmentioning
confidence: 99%